Struktur Pendanaan dan Pola Bisnis Sektoral pada Platform Crowdfunding Syariah di Indonesia - Asep Koswara; Bayu Anggara Putra (Balance: Media Informasi Akuntansi dan Keuangan, 2026)
This study examines the funding structure and sectoral business patterns in Islamic crowdfunding platforms in Indonesia, focusing on investment listings from Shafiq.id. The research aims to identify how funding characteristics such as total investment, number of investors, and financing tenor relate to different business sectors. Using a descriptive and exploratory quantitative approach, the study analyzes project-level data to uncover patterns of capital allocation and investor preferences. The findings reveal that although the number of projects is relatively evenly distributed across sectors, funding is disproportionately concentrated in specific sectors, particularly trade and project-based businesses. This indicates a tendency among investors to favor sectors with larger capital requirements and potentially higher returns. Additionally, the results suggest a relationship between sector type and funding characteristics, reflecting a risk-return trade-off within the framework of Sharia principles. The study highlights the importance of sectoral analysis in understanding investment behavior and provides insights for platform managers and investors in optimizing portfolio strategies within Islamic crowdfunding ecosystems.